SRDigital: proposta de um modelo baseado na linguagem natural e controlada como instrumentos de apoio ao agente computacional do processo de referência - Souza, Patrícia da Silva Moreno e [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Nowadays we can see the growth of users who use the Internet to conduct their search for information because the Web is a major means of obtaining information and current scientific development in general. As a result, the more information is available on the Web, the more likely that the user needs the services provided by the library, for instance, the digital reference service to their search and information retrieval. Considering that many users interact with the system in natural language, it becomes a research problem that needs to be discussed, from a model of digital reference service using natural and controlled language as tools to support the agent's computational process of reference. Besides, it demonstrates how semiotic engineering could contribute to the development of interfaces because interfaces without structures, development techniques and analysis can cause problems of interaction and use. Based on the referral process, this thesis has the purpose of providing a service that can be accessible to users, inviting their participation and collaboration. It was necessary to consider issues such as flexibility and adaptability to new media and the new user profile, education in the access to online resources, cooperation, speed and efficiency. The goal was to add Web 2.0 services with the services offered by the reference service in an attempt to leverage the most from this new environment, as well as to reflect and discuss the referral process by Denis Grogan in a recovery environment based on a digital environment. It is also crucial to mention in addiction the need for addressing assessment techniques to semiotic engineering evaluation and validation of interactive interfaces. The methodological approach... (Complete abstract click electronic access below)

Nos dias de hoje vemos o crescimento de usuários que utilizam a Internet para realizarem suas buscas por informações, pois a Web é um dos principais meios de obterem informações de desenvolvimento científico e atualidades em geral. Portanto, quanto mais informação estiver disponível na Web maior será a probabilidade de que o usuário necessite dos serviços prestados pela biblioteca, como por exemplo, o serviço de referência digital para suas buscas e recuperação da informação. Visto que, muitos usuários interajem com o sistema em linguagem natural apresenta-se como problema de pesquisa a necessidade de discutir, a partir de um modelo do serviço de referência digital a utilização da linguagem natural e controlada como instrumentos de apoio ao agente computacional do processo de referência. Além disso, demonstrar como a engenharia semiótica poderia contribuir para o desenvolvimento de interfaces, pois interfaces sem estruturas, técnicas de desenvolvimento e análises podem causar problemas de interação e usabilidade. Com base no processo de referência, esta tese tem como proposta fornecer um serviço que seja acessível aos usuários convidando-o a participação e colaboração. Considerando questões como: flexibilidade e adaptabilidade às novas mídias e ao perfil do novo usuário, educação no acesso a recursos on-line, cooperação, rapidez e eficiência. Tendo como objetivo agregar os serviços da Web 2.0 com os serviços oferecidos pelo serviço de referência na tentativa de potencializar ao máximo este novo ambiente. O objetivo geral desta pesquisa é refletir e discutir o processo de referência de Denis Grogan em um ambiente de recuperação baseado num ambiente digital. Além disso, abordar técnicas...
Keywords: Sistemas de recuperação da informação; Serviços da Web; Interfaces de usuario (Sistema de computador)